A Novel Intraurethral Device Diagnostic Index to Classify Bladder Outlet Obstruction in Men with Lower Urinary Tract Symptoms. (25th December 2008) - Reis, Leonardo O.; Barreiro, Guilherme C.; Prudente, Alessandro; Silva, Cleide M.; Bassani, José W. M.; D'Ancona, Carlos A. L.
Abstract : Objectives . Using a urethral device at the fossa navicularis, bladder pressure during voiding can be estimated by a minimal invasive technique. This study purposes a new diagnostic index for patients with lower urinary tract symptoms (LUTSs). Methods . Fifty one patients presenting with LUTSs were submitted to a conventional urodynamic and a minimal invasive study. The results obtained through the urethral device and invasive classic urodynamics were compared. The existing bladder outlet obstruction index (BOOI) equation that classifies men with LUTSs was modified to allow minimal invasive measurement of isovolumetric bladder pressure in place of detrusor pressure at maximum urine flow. Accuracy of the new equation for classifying obstruction was then tested in this group of men. Results . The modified equation identified men with obstruction with a positive predictive value of 68% and a negative predictive value of 70%, with an overall accuracy of 70%. Conclusions . The proposed equation can accurately classify over 70% of men without resorting to invasive pressure flow studies. We must now evaluate the usefulness of this classification for the surgical treatment of men with LUTSs.